Health related quality of life of special education school children with autism spectrum disorder and/or intellectual disability disorder - Tay, Shi Ying (Nanyang Technological University, 2021)
In line with Singapore’s goal to improve the quality of life of individuals with disabilities, this study sought to understand the health related quality of life (HRQoL) of children with autism spectrum disorder (ASD) and/ or intellectual disability disorder (IDD) in Singapore. The present study seeks to address the following questions: (1a) What is the level of HRQoL of children with ASD and/or IDD in Singapore? (1b) How do levels of HRQoL differ between children with ASD, IDD, and comorbid ASD and IDD in Singapore? (2) What are the factors that predict HRQoL of children with ASD and/or IDD in Singapore? We used data collected by the TRAN-SEN study at NIE and conducted a secondary analysis. The sample comprised of 119 children with ASD and/or IDD who are attending special education schools in Singapore. The findings suggest that children with ASD and/or IDD in Singapore experience significantly lower HRQoL than typically developing children, and HRQoL is equally poor among the different groups. The predictors of HRQoL were: diagnosis, adaptive behaviour, parental income and depressive symptoms in parents. Specifically, children with a comorbid diagnosis of ASD and IDD, who exhibit low levels of adaptive behaviour, whose parents have high levels of income and significant depressive symptoms experienced lower HRQoL. Notably, age, gender and behavioural problem of the child did not predict HRQoL. Practical implications and directions for future research are discussed.